Opportunities For Language And Thinking In The Development Of Society - Djavotova Ohista Djamol qizi (Zien Journals, 2024)
The article reveals the role and significance of language as an object of philosophical research in the development of logical thinking, science. It is especially important that the relationship of language to logic is analyzed within the framework of Philosophical Studies. However, the influence of language on the achievement of maturity, the formation of young people of high potential, the expansion of the framework of logical thinking, the increase in intellectual opportunities is considered very important. The study of the constructive possibilities of language in the development of society on the basis of philosophical laws is important in the science of today's times.
Keywords: language; logic; logical; thinking